2021
DOI: 10.3390/pharmaceutics13050684
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Trastuzumab Biosimilars for the Treatment of HER2-Positive Breast Cancer: A Real-World Experience from a Cancer Center

Abstract: Background: The introduction of trastuzumab biosimilars in clinical practice plays an important role in promoting the sustainability of healthcare systems. By contrast, the switching process can be challenging to the clinics. This survey describes the switching process at a National Cancer Institute over a period of 2 years. Methods: Data regarding all trastuzumab-based regimens for breast cancer (BC) from 1 January 2019 and 31 December 2020 were extracted from both adverse drug reactions (ADRs) reporting syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A change in use to trastuzumab biosimilars for some patients may also have contributed to high use among women diagnosed in 2018 and 2019, demonstrating the continuing influence of drug development and approvals on uptake of existing approved drugs. This finding is echoed in an Italian study which reported increased use, with trastuzumab biosimilars contributing to around one-third of trastuzumab-based treatment among patients diagnosed in more recent years [27]. Additionally a review of biosimilars highlighted the value of their inclusion in trastuzumabbased treatment in increasing access to anti-HER2 therapies, particularly in relation to cost-saving [28].…”
Section: Uptake Of Drugs Recommend By Nice For Use Following Relapse/...mentioning
confidence: 99%
“…A change in use to trastuzumab biosimilars for some patients may also have contributed to high use among women diagnosed in 2018 and 2019, demonstrating the continuing influence of drug development and approvals on uptake of existing approved drugs. This finding is echoed in an Italian study which reported increased use, with trastuzumab biosimilars contributing to around one-third of trastuzumab-based treatment among patients diagnosed in more recent years [27]. Additionally a review of biosimilars highlighted the value of their inclusion in trastuzumabbased treatment in increasing access to anti-HER2 therapies, particularly in relation to cost-saving [28].…”
Section: Uptake Of Drugs Recommend By Nice For Use Following Relapse/...mentioning
confidence: 99%